2003
DOI: 10.1097/00002030-200311210-00010
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of myocardial infarction with duration of protease inhibitor therapy in HIV-infected men

Abstract: Our results point to a duration-related effect relationship between PI and MI, with a higher MI incidence rate among men exposed to PI for 18 months or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
312
1
14

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(333 citation statements)
references
References 26 publications
6
312
1
14
Order By: Relevance
“…[4][5][6]9,10,29,30 Therefore, the study of mechanisms involved in HAART-associated cardiovascular mortality may be relevant for the development of new drugs to treat HIV infection. In this study, we showed for the first time that HAART decreases the circulating levels of TIMP-1 by approximately 65%, thus increasing pro-MMP-9/TIMP-1 ratios by 34%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6]9,10,29,30 Therefore, the study of mechanisms involved in HAART-associated cardiovascular mortality may be relevant for the development of new drugs to treat HIV infection. In this study, we showed for the first time that HAART decreases the circulating levels of TIMP-1 by approximately 65%, thus increasing pro-MMP-9/TIMP-1 ratios by 34%.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, HAART has also been associated with the development of metabolic complications, including dyslipidemia, insulin resistance and altered fat distribution, and with the increased concern regarding enhanced cardiovascular risk. [3][4][5][6][7][8][9][10] Indeed, endothelial dysfunction can be caused by the virus itself and by protease inhibitors, and the thymidine analogs (zidovudine and stavudine) may increase superoxide production, thus affecting the endothelial function. 11 Although the increased cardiovascular risk associated with HAART is probably because of adverse metabolic alterations that are known risk factors for cardiovascular diseases, other mechanisms may also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a significant linear correlation between TG/HDL ratio and LDL size (r=-0.36 p<10 -4 ) observed in our study, a value of 1.5 was identified as the significant cut-off for distinguishing HIV+ patients having higher CIMT. Furthermore, other studies such as the DAD collaboration reported an 13 independent effect of dyslipidemia on myocardial infarction in HIV+ patients underlining the need to analyse more deeply those lipid abnormalities 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Because classical risk factors do not account for all atherosclerosis risk in HIV+ patients, a search for non-classical could be of interest. Some of them could be directly related to HIV infection or its treatment such as duration of c-ART, time from HIV diagnosis, HIV plasma viral load or lipodystrophy [12][13][14][15] . Other ones including non-high density lipoprotein (HDL) cholesterol, Triglyceride (TG) to HDL ratio, apolipoprotein B (apoB), LDL size, inflammation or oxidative stress could be related to metabolic disorders such as metabolic syndrome (MS) and lipid triad (LT).…”
mentioning
confidence: 99%
“…In addition to the high prevalence of risk factors for cardiovascular diseases such as smoking, arterial hypertension, and elevated triglycerides and VHDL cholesterol among persons with HIV/ AIDS 18 , studies suggest that HAART and the chronic inflammation characterizing HIV infection are associated with greater risk of cardiovascular diseases in persons with HIV/AIDS 19,20 . Some studies have shown greater risk of cardiovascular events in persons with HIV/AIDS and on HAART as compared to those without treatment 21,22 .…”
Section: Discussionmentioning
confidence: 99%